Evaluation of the Implementation of the OBE Curriculum with the CIPP Model (Context, Input, Process, and Product) at the Faculty of Economics State University of Medan - Choms Gary Ganda Tua Sibarani; Jabal Ahsan; Andi Taufiq Umar (Edumaspul: Jurnal Pendidikan, 2024)
The curriculum is the primary key to the success of learning, so it is necessary to evaluate, improve, and analyze the implementation of the curriculum. In this study, the researcher examines the implementation of the OBE (Outcome Base Education) Curriculum at the Faculty of Economics, State University of Medan, using the CIPP (context, input, process, product) evaluation model. The methods used in this study are quantitative and qualitative with a mixed-method approach. This research involved second-semester students in three majors at FE Universitas Negeri Medan, namely the accounting department, the economics department, the management department, and several lecturers representing the faculty. The data collection technique uses a questionnaire as the main instrument, and the data is analyzed using the percentage of respondents' achievement rate (TCR Test) for quantitative data. Interview data collection as a supporting tool was analyzed using Miles and Huberman data analysis techniques, namely data reduction, data display, and conclusion or verification. The findings are as follows: 1) The context dimension shows "excellent" results by obtaining an average score of 90,8. 2) The input dimension showed " excellent " results by obtaining an average score of 88,9. 3) The process dimension showed " excellent" results by obtaining an average score of 91,2. 4) The product dimension showed " excellent " results by obtaining an average score of 88,7. Based on the findings, the researcher recommends improvements in each dimension so that the curriculum implementation at OBE in FE Universitas Negeri Medan is in accordance with our expectations